Effect of cow dung and urea on some soil properties and growth of Amaranthus in Bennubyen flood plain in Wukari - Yakub, Waizah; Alex, Onwu Clement (International Journal of Sustainable Agricultural Research, 2024)
A field trail was conducted in Bennubyen flood plain of Wukari, Taraba State, Nigeria to evaluate the effect of cow dung and urea on some soil properties and growth of Amarathus hybridus, The experiment was laid out in a Randomized complete block design (RCBD), with seven treatments replicated three times, T1 receives 30 t/ha, T2 received 150 kg/ha, T3 received 75kg/ha + 30 t/ha, T4 received 15 t/ha + 150 kg/ha, T5 received 15 t/ha T6 received 75 kg/ha, and T7 received no treatment and serve as the control. The pre cropping soil analysis when compared with post cropping soil analysis showed that, application of organic and inorganic fertilizers improved soil OC, OM, N %, ECEC, and available P, while decrease was observed on the pH, Zn, Cu, Mn and Fe. The results on the growth parameters and yield of Amarathus hybridus were significantly (p<0.05) improved by the applications of urea and cow dung, the highest increase was observed on the treatment with cow dung (30 t/ha), urea (150 Kg/ha) and cow dung 15 t/ha combined with urea (75kg/ha). The use of urea and cow dung is therefore essential in increasing Amaranthus hybridus yield. Since no significant difference was found at 30 t /ha of cow dung, 150kg/ha of urea and 15t/ha of cow dung and 75kg /ha of urea combined, use of cow dung at the rate of 30t/ha is recommended.